PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN PT IRA KONSULTAN INDONESIA JAKARTA SELATAN - Hesti Dwi Lestari; Iskandar Zulkarnain (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the effect of financial and non-financial compensation on job satisfaction of PT Ira Konsultan Indonesia employees both partially and simultaneously. The research method used is a quantitative method. The population in this study were 50 employees of PT Ira Konsultan Indonesia with a sample size using the Slovin formula with a margin of error of 5%. A sample of 40 employees was obtained as research respondents. The data collection technique was by distributing questionnaires. The data analysis method used multiple linear regression tests, partial t tests and simultaneous f tests. The results of this study indicate that there is a positive influence between financial improvements on job satisfaction of PT Ira Konsultan Indonesia employees, this is evidenced by the results of the t-count value of 5.347> t-table 2.024 with a significant value of 0.000 <0.05. There is a positive and significant influence between non-financial improvements on job satisfaction of PT Ira Konsultan Indonesia employees, this is evidenced by the results of the t-count value of 5.055> t-table 2.024 with a significant value of 0.000 <0.05. Simultaneously, there is a positive and significant influence between financial and non-financial improvements on employee job satisfaction at PT Ira Konsultan Indonesia, this is proven by the results of multiple linear regression of Y = 2.789 + 0.572 X1 + 0.543 X2, the coefficient of determination value is 53.2%, and the calculated f value is 21.025 > f table 3.25 with a significant value of 0.000 < 0.05. Keywords: Financial Compensation, Non-Financial Compensation, Job Satisfaction